2019
DOI: 10.1002/jcp.28400
|View full text |Cite
|
Sign up to set email alerts
|

TRIM72 contributes to cardiac fibrosis via regulating STAT3/Notch‐1 signaling

Abstract: Cardiac fibrosis is a pathophysiological process characterized by excessive deposition of extracellular matrix. We developed a cardiac hypertrophy model using transverse aortic constriction (TAC) to uncover mechanisms relevant to excessive deposition of extracellular matrix in mouse myocardial cells. TAC caused upregulation of Tripartite motif protein 72 (TRIM72), a tripartite motif‐containing protein that is critical for proliferation and migration. Importantly, in vivo silencing of TRIM72 reversed TAC‐induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The activation of STAT3 via phosphorylation by Janus kinases (JAKs) has been demonstrated in a variety of disease models, including models of Alzheimer's and Huntington's diseases [29], cerebral ischemia [30], and SCI [31]. A large number of studies have indicated a strong association between Notch and JAK/STAT3 signaling, and a change in Notch expression can alter STAT3 phosphorylation and activity [32][33][34]. However, whether JAK/STAT3 signaling participates in the suppressive effects of MSCs on Notch1 expression after SCI is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of STAT3 via phosphorylation by Janus kinases (JAKs) has been demonstrated in a variety of disease models, including models of Alzheimer's and Huntington's diseases [29], cerebral ischemia [30], and SCI [31]. A large number of studies have indicated a strong association between Notch and JAK/STAT3 signaling, and a change in Notch expression can alter STAT3 phosphorylation and activity [32][33][34]. However, whether JAK/STAT3 signaling participates in the suppressive effects of MSCs on Notch1 expression after SCI is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated a strong association between Notch and Stat3 signaling. Notably, a change in Notch expression can alter Stat3 phosphorylation and activity [28,35,36], suggesting that Notch signaling can alter astrocyte phenotype by affecting Stat3 activity and function.…”
Section: Introductionmentioning
confidence: 99%
“…STAT3 has a key role in in ammation that underlies cardiovascular disease and impacts on cardiac structure and function and is important for maintaining endothelial cell function and capillary integrity with aging and hypertension [32]. Besides, STAT3 also involves the cardiac hypertrophy and brosis in TAC mouse models [33,34]. Duerr GD et al suggested that in the cardiac hypertrophy group CCL2 and CXCL8 had increased expression and anti-in ammatory IL-10 had a suppression which indicated the persistent in ammatory reaction [35].…”
Section: Discussionmentioning
confidence: 99%